High Prevalence of Salmonella spp. in Ready-to-Eat Artisanal Pork Sausages Sold at Food Outlets in Quindío, Colombia - Elizabeth Jaramillo-Bedoya; Liliana Janeth Flórez-Elvira; Iván Darío Ocampo-Ibáñez (Pathogens)
Non-typhoidal salmonellosis is a foodborne disease caused by Salmonella spp. Most outbreaks of this disease are commonly associated with consuming contaminated meat products, hence the importance of monitoring ready-to-eat artisanal pork sausages for the presence of these bacteria. A total of 494 samples of grilled and smoked barbecue artisanal pork sausages were collected at food outlets from 12 municipalities of the Department of Quindío, Colombia, between 2017 and 2022. Salmonella spp. was identified using VIDAS® Easy SLM and confirmed through API® 20 E. Salmonella spp. was detected in 260 samples (52.6%), and the highest rates of contamination were found in Armenia (65.7%), Salento (65.2%), Circasia (57.7%), and Calarcá (56.4%). The highest proportion of these samples positive for Salmonella spp. was ready-to-eat smoked barbecue artisanal sausages (68.8%) sold by street vendors (58.4%) from 12 municipalities of the Department of Quindío. A significant association was observed between the municipality and contamination of samples with Salmonella spp. However, no link was found between the sampling year and the presence of the bacteria. This is the first study aimed at monitoring the presence of Salmonella spp. in artisanal pork sausages sold in the municipalities of the Department of Quindío over a 6-year period, and findings revealed very high percentages of contamination. Although Colombian legislation establishes sanitary and safety requirements for meat production, the presence of Salmonella spp. in artisanal sausages remains a persistent public health threat in developing countries.